Natural Gas Utilization through Domestic Gas Distribution in Nigeria - SI, Onwukwe; Duru, U I; Ikpeka, P M (Journal of Advanced Research in Petroleum Technology & Management, 2021)
There has been persistent effort by the government and the operating oil companies to develop gas infrastructure in Nigeria. These have led to the steady reduction in gas flares in the oil producing areas. If the country is to practically eliminate gas flaring by 2020 when it envisage to be among the twenty developed country in the world (Vision 202020), then further avenues of gas utilization should be explored. This article therefore examines the feasibility and technical features of increasing the domestic gas consumption through effective transmission and distribution of natural gas to indigenous local consumers. A case study of natural gas distribution from an oil field of Izombe to Urban city of Owerri, Imo State, was analyzed for economic viability.